Dari Aturan ke Hasil Pelayanan: Menjelaskan Kinerja Pelayanan Administratif melalui Disiplin Kerja di Pemerintah Daerah - Hendrawan Kamaru; Asna Aneta; Muchtar Ahmad; Yakob Noho Nani; Alfiyah Agussalim (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2026)
This study examines how work discipline shapes administrative service performance at the Posigadan District Office, South Bolaang Mongondow Regency. Previous studies generally identify a positive relationship between work discipline and employee performance but provide limited explanations of the mechanisms through which discipline influences public service outcomes. This study aims to explore these mechanisms using a qualitative case study approach. Data were collected through in-depth interviews, direct observations, and document analysis involving government officials and supporting administrative records. The findings reveal that work discipline operates through five interrelated dimensions: adherence to working hours, compliance with established procedures, observance of work standards, thoroughness in task execution, and a strong work ethic. These dimensions collectively influence service reliability, consistency, predictability, administrative accuracy, and citizens’ overall service experience. The study further demonstrates that disciplined work behavior strengthens accountability, improves responsiveness, and supports the delivery of more effective and efficient public services. Rather than viewing work discipline merely as individual compliance with organizational regulations, this research argues that discipline functions as a microgovernance mechanism that translates formal institutional arrangements into tangible service outcomes. The findings contribute to the literature on Street-Level Bureaucracy and Behavioral Public Administration by providing empirical evidence that frontline behavioral capacity plays a critical role in shaping administrative service performance in local government organizations. The study also offers practical insights for improving public service quality through strengthening organizational discipline and employee accountability.